Pelatihan Perbanyakan Bibit Tanaman Durian bagi Petani di Desa Jurong Kecamatan Sawang, Kabupaten Aceh Utara: Durian Seedling Propagation Training for Jurong Village Farmers, Sawang Subdistrict, North Aceh District - Ismadi, Ismadi; Handayani, Rd Selvy; Rafli, Muhammad; Lukman, Lukman; Fridayanti, Nelly; Putra, Eric Erdiyansyah; Nasution, Chairil Adha (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Durian is one of the potential crops to be developed in Jurong Village, Sawang District, North Aceh Regency. Sawang District is known as one of the centers of local durian production in Aceh which has an agroecosystem that is very suitable for durian plants. However, durian cultivation is still hampered by the unavailability of quality seeds suitable for the local agroecosystem. In addition, farmers' knowledge and skills are still limited in producing durian seeds, especially local durian seeds. This community service activity was carried out in Jurong Village, Sawang District, North Aceh Regency from July to September 2024 The community service activities carried out can increase the knowledge and skills of farmers in identifying prospective scion and rootstock parent trees, grafting techniques, planting, and maintenance of durian plants.